MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA MELALUI MEDIA SEDOTAN LIMUN SISWA KELAS I MIN KERTAK HANYAR II KECAMATAN KERTAK HANYAR KABUPATEN BANJAR - Maslianiwati Maslianiwati (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2015)
This research aims to increase the activity of teachers and students in teaching and learning of Mathematics “Addition Numbers Two Digits” without Saving and In Saving, as well as improving student learning outcomes in the fisrt grade of MIN KertakHanyar II in Mathematics through the teaching aids “straw of lemonade”. The method used in this research is descriptive qualitative method of classroom action research that conducted in two cycles. At each cycle (cycle 1 and cycle 2) consists of one session. The subjects were Mathematics teacher in the 1st grade and 1st grade students of MIN Kertak Hanyar II in the second semester of the academic year 2013-2014. The number of students are 32. Collecting data in this study were obtained through observation techniques, test, documentation; data analysis techniques were used are based on average and percentage. The results of this research indicates that the implementation of lemonade straws media on subjects Mathematics performing well. (1) The results of the first cycle of teacher activity at 76.66%, which is enough classification. In the second cycle increased to 93, 33% of which are in very good classification. (2) Activity student in first cycle at 70%, which is enough classification. In the second cycle increased to 90%, which is at a very good classification. (3) The results of the first cycle of student learning classical completeness initially acquire 68.75% in less classification. In the second cycle increased to 93.75% with an excellent classification.